(3GdaQOhSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdCehQ GdehLhO ajfG dcd efgG eGgjI hghjI hdjSJ eGgjJg ghjJg s
(3BNQgG (B:s
(3Gf cd ReGf abO jhLO ReGf JCNQ Yfg hdG jhLO Yf GdMb gh agh WGdH Cj WGdH Gdcd Edi Gdfjd efg s
(3Vef eLehY , JQJjHgG (B: 8s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs